Itinerário formativo da ética do discurso de Karl Otto Apel - Silva, Antonio Wardison Canabrava da (2013)
This thesis aims to identify and analyze the itinerary that led Karl Otto Apel to his Ethics of Discourse. In this perspective, this research, which is critical-analytical in character, departs from an inquiry that will guide his whole reflection: what is the way that was covered by Apel to elaborate his ethical postulate? This inquiry will try to understand how Apel built a rational ethics amid discussions waged with modern and contemporary philosophers. So as to accomplish this task, Chapter One will analyze the problem of the ethical grounding in the Age of Science, characterized by the situation of the human being as an ethical problem, due to the paradox of the dearthiness and abnegation of a rational ethics and due to the philosophical currents that defy a possible ethical grounding: modern Analytical Philosophy, Wittgenstein s Logic of Science, Hans Albert s Decisionism, Max Weber s Rationality and Ethical postulates, and methodological Solipsism. Chapter Two will present the hermeneutical-semiotic transformation of Transcendental Philosophy, by analyzing Apel s critical perspective regarding the Kantian factum of Reason; the Hermeneutical Turn in the transformation of Transcendental Philosophy and, with that, Heidegger s and Gadamer s Phenomenology, as well as Apel s critique of those two thinkers; the Semiotic transformation of Transcendental Philosophy brought about by Peirce, the postulate of the Community of Inquiry and Interpretation, and Apel s critique of Peirce s Scientifism and the Transcendental-Hermeneutical concept according to Apel s understanding. Chapter Three will present the architecture of Apel s Ethics of Discourse, understood by its Pragmatic-Transcendental dimension, the A (ideal) and B (real) parts of his Ethics of Discourse and the existing dialogicity between, the transcendental reflection as philosophy s last grounding, and Kohlberg s particular contribution to Apel s ethical grounding; and, lastly, the relevance of Apel s Ethics of Discourse to the contemporary world. In sum, this thesis will try to identify and analyze the course covered by Apel to elaborate his ethical-philosophical proposal